1996
DOI: 10.1046/j.1365-2141.1996.4931034.x
|View full text |Cite
|
Sign up to set email alerts
|

Progression from myelodysplastic syndrome to acute lymphoblastic leukaemia with Philadelphia chromosome and p190 BCR‐ABL transcript

Abstract: We describe a patient with Philadelphia chromosome (Ph1)-positive acute lymphoblastic leukaemia (ALL) who developed it 2.5 years after being diagnosed with myelodysplastic syndrome (MDS). The patient initially had refractory anaemia (RA), but progressed to refractory anaemia with excess blasts (RAEB) 2 years later, that terminated in ALL. An immunophenotypic analysis of the lymphoblasts revealed CD10 and CD19 positive cells. The karyotype was normal 46,XY in RA phase, 46,XY,20q-during the RAEB phase, and 46,XY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 9 publications
(10 reference statements)
1
14
0
Order By: Relevance
“…These findings support the idea that BCR-ABL is a secondary event, like in the case reported by Bornhäuser et al 6 Similarly, we and others reported some cases with a secondary Ph-chromosome acquired during the course of a myelodysplastic syndrome. 9,10 In summary, we confirmed that BCR-ABL rearrangement and JAK2V617F mutation may occur concomitantly in hematopoietic cells of a single patient at initial presentation. After the onset of IM therapy, the CML clone became undetectable, while the JAK2V617F-mutated clone continued to grow, suggesting that the PV erythroid progenitors were not inhibited by a 400 mg daily dose of IM.…”
supporting
confidence: 61%
“…These findings support the idea that BCR-ABL is a secondary event, like in the case reported by Bornhäuser et al 6 Similarly, we and others reported some cases with a secondary Ph-chromosome acquired during the course of a myelodysplastic syndrome. 9,10 In summary, we confirmed that BCR-ABL rearrangement and JAK2V617F mutation may occur concomitantly in hematopoietic cells of a single patient at initial presentation. After the onset of IM therapy, the CML clone became undetectable, while the JAK2V617F-mutated clone continued to grow, suggesting that the PV erythroid progenitors were not inhibited by a 400 mg daily dose of IM.…”
supporting
confidence: 61%
“…Little is known about the molecular events in Ph-positive transformed MDS. An M-bcr rearrangement was detected in refractory anaemia with excess of blasts (RAEB) (Nakamura et al, 1991 rearrangement may occur in MDS and its accelerated phase, as described in three cases of RAEB, one of which unexpectedly progressed to common ALL (Kohno et al, 1996;Lesesve et al, 1996). In another case, both p190 and p210 bcr-abl were demonstrated in the course of a myeloblastic transformation (Katsuno et al, 1994).…”
Section: Discussionmentioning
confidence: 93%
“…Neoplastic transformation can occur at various levels of stem cell development (Kohno et al. , 1996).…”
Section: Discussionmentioning
confidence: 99%